Kiss of the rose princess. Volume 8 - Shouoto, Aya, 1977- (VIZ Media, LLC, 2016)
High school student Anise Yamamoto is the Rose Princess of four handsome Rose Knights. Anise and her knights are fighting to defeat the Fake Rose Knights, but Kaede is losing to Shiden, the powerful Purple Rose, and faces death. The time has come for Anise to awaken him with a kiss.